Symbiotic Relationships between Nitrogen-fixing Bacteria and Leguminous Plants Ecological and Evolutionary Perspectives: A Review - Chellem, Sushma Raj; Kishore, Chiriki Vasantha Lakshmana; Reddy, Gurrala Sai Vamsi; Akshay, D. V. S.; Kalpana, Kavuri; Lavanya, Purimetla; Choragudi, Kavya Harshita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The symbiotic relationships between nitrogen-fixing bacteria and leguminous plants play a Important role in enhancing soil fertility, boosting crop yields, and promoting sustainable agricultural practices. The molecular and biochemical mechanisms underpinning these interactions, including signal exchange, root nodule formation, and metabolic integration. The co-evolution of legumes and rhizobia, driven by reciprocal selective pressures, has resulted in highly specialized and efficient symbiotic relationships. Genetic adaptations in legumes, such as the evolution of receptor-like kinases and transcription factors, facilitate the establishment and maintenance of these symbioses. The evolutionary divergence among nitrogen-fixing bacteria, influenced by host specificity and environmental factors, has led to a diverse array of rhizobial strains with varying symbiotic capabilities. Horizontal gene transfer has further contributed to the spread of symbiotic traits, enhancing the adaptability and ecological success of rhizobia. In agricultural contexts, the benefits of symbiotic nitrogen fixation are substantial, reducing reliance on synthetic fertilizers and improving soil health. Sustainable practices such as crop rotation, intercropping, and cover cropping with legumes enhance soil nitrogen levels and overall farm productivity. Advances in genetic engineering and biofertilizer technology offer promising avenues to optimize symbiotic efficiency and extend nitrogen-fixing capabilities to non-leguminous crops. Challenges remain, including the need for effective delivery systems for biofertilizers and the variability of symbiotic performance under different environmental conditions. Future research should focus on understanding soil microbial interactions and developing resilient rhizobial strains. By leveraging these natural processes, we can enhance agricultural sustainability, ensuring food security and environmental health for future generations. This comprehensive review underscores the critical importance of nitrogen-fixing symbioses in agriculture and ecosystem management.